2017
DOI: 10.1037/xlm0000328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid forgetting results from competition over time between items in visual working memory.

Abstract: Working memory is now established as a fundamental cognitive process across a range of species. Loss of information held in working memory has the potential to disrupt many aspects of cognitive function. However, despite its significance, the mechanisms underlying rapid forgetting remain unclear, with intense recent debate as to whether it is interference between stored items that leads to loss of information or simply temporal decay. Here we show that both factors are essential and interact in a highly specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
103
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 73 publications
(113 reference statements)
25
103
5
Order By: Relevance
“…Next, we explored how selection impacts the neural representations of items in working memory. As noted above, selection improves working memory accuracy 5,[27][28][29] (Fig. 1E).…”
supporting
confidence: 57%
“…Next, we explored how selection impacts the neural representations of items in working memory. As noted above, selection improves working memory accuracy 5,[27][28][29] (Fig. 1E).…”
supporting
confidence: 57%
“…3E,F). This is consistent with behavioral studies that have shown increases in memory error, even below working memory capacity limits [Bays et al, 2009;Ma et al, 2014;Pertzov et al, 2017;Rademaker et al, 2018].…”
Section: Interference Between Memory Representations Imposes a Capacisupporting
confidence: 91%
“…Consistent with behavioral studies [Bays et al, 2009;Ma et al, 2014;Pertzov et al, 2013Pertzov et al, , 2017Rademaker et al, 2018;Zhang and Luck, 2008], errors in working memory increased with the number of items held in memory ( Fig. 3C and S2A).…”
Section: Interference Between Memory Representations Imposes a Capacisupporting
confidence: 86%
“…the proportion of valid to invalid retro-cue trials). Typically, studies that failed to observe invalid cueing costs used lower retrocue reliabilities 31,40,42 than studies that observed invalid cueing costs 32,37,39,43 . In a behavioral study, we observed invalid cueing costs only when the retro-cue had a high reliability (i.e., 80% valid), but not when it had a lower, but still above-chance reliability (i.e., 50% valid, with chance level being at 25% in both conditions).…”
Section: Introductionmentioning
confidence: 99%